2021
DOI: 10.15381/rpb.v28i1.19742
|View full text |Cite
|
Sign up to set email alerts
|

Polimorfismos de nucleótido simple (PNSs) del gen MC1R en alpacas negras y marrones

Abstract: En alpacas los fenotipos del color de vellón tienen diferentes terminologías que induce a una confusión dentro del color marrón y sus tonalidades, el que requiere de una mejor descripción y cuantificación. En consecuencia los objetivos del estudio fueron cuantificar el color de fibra e identificar los PNSs informativos del gen MC1R (receptor 1 de melanocortina) en alpacas marrones y negras. Un fenotipo vicuña (n=14) y cuatro fenotipos de alpacas (n=79), marrón claro, marrón oscuro, marrón-negro y negro fueron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
1
2
1
Order By: Relevance
“…The same situation was also determined in llamas, guanacos, and vicuñas analyzed where all the animals were of the CC genotype. These results differ from those found by the authors in [ 21 , 34 ] who did not see white alpacas with the TT genotype and only found heterozygous white alpacas. The authors in [ 20 , 29 ] mentioned genotypes similar to those reported in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The same situation was also determined in llamas, guanacos, and vicuñas analyzed where all the animals were of the CC genotype. These results differ from those found by the authors in [ 21 , 34 ] who did not see white alpacas with the TT genotype and only found heterozygous white alpacas. The authors in [ 20 , 29 ] mentioned genotypes similar to those reported in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Mutations affecting promoter regions and specific transcription factors have increased melanin synthesis [ 38 ]; 3′ untranslated regions (3′ UTRs) contain a critical class of noncoding variants that might impact posttranscriptional and translational processes [ 39 ]. Although one of these polymorphisms (3′+5T > C) was reported in [ 19 , 34 ], it was not significant compared to the results of the present study.…”
Section: Discussioncontrasting
confidence: 96%
“…Las coordenadas del espacio CIE L*a*b* definen los parámetros colorimétricos como la luminosidad, intensidad y tonalidad de la fibra (Pinares et al, 2021;Cruz et al, 2021). El parámetro K/S es un indicador de la intensidad del color.…”
Section: Introductionunclassified
“…Domestic South American camelids exhibit a diversity of pigmentation patterns. Alpaca fiber is the most valuable product used in the textile industry and has a wide variety of natural colors (Oria et al, 2009;Jost et al, 2020), as is shown by the continuous variation in pigmentation found in Peruvian alpacas (Cruz et al, 2021;Pinares et al, 2021) and through chemical analysis (Wang et al, 2005;Cransberg et al, 2013). However, the production of colored fiber has decreased over time, directly influenced by the higher price of white fiber, and exacerbated by the erosion of genetic diversity in the Andean camelid population (Antonini and Vinella, 1997;Aragoń and Mamani, 2018;Anello et al, 2022).…”
Section: Introductionmentioning
confidence: 99%